Pengaruh Pembelajaran Berbasis Lingkungan Terhadap Minat Belajar Siswa Kelas V SD Islamiyah Tahun Ajaran 2023/2024 - Hariati, Hariati; Lubis, Rizka Hidayah Husin; Hariati, Emy (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2024)
This study investigates the impact of the Environment-Based Learning Model on students' interest in learning in Class V at Islamiyah Private Elementary School during the 2023/2024 academic year. Using a quantitative research approach, the study employed experimental and control groups to measure the effectiveness of the learning model. The results indicate that the environment-based learning model significantly enhances students' interest in learning. The experimental group, which utilized this model, achieved an average score of 82.2 with a standard deviation of 9.06, whereas the control group obtained an average score of 51.67 with a standard deviation of 7.18. Hypothesis testing yielded a calculated t-value of 0.06, which, when compared to the t-table value (0.245 at a 5% significance level), confirmed the acceptance of the hypothesis. These findings suggest that integrating environment-based learning strategies can effectively improve students' engagement and academic motivation.